2021
DOI: 10.1039/d0sc06122k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of covalent binding of ibrutinib to Bruton's tyrosine kinase revealed by QM/MM calculations

Abstract: Ibrutinib is the first covalent inhibitor of Bruton’s tyrosine kinase (BTK) to be used in the treatment of B-cell cancers. Understanding the mechanism of covalent inhibition will aid in the...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 40 publications
1
53
2
Order By: Relevance
“…Some classes of inhibitors of SARS-CoV-2 M pro , such as Michael acceptors and ketoamides, , also require a deprotonated Cys145 to covalently bind the active site. Diverse binding mechanisms between inhibitors and enzymes featuring an active-site cysteine have been reported, either involving a direct PT reaction between the inhibitor and the cysteine or requiring a PT reaction from the cysteine to a protein base prior to the binding reaction . In the case of SARS-CoV-2 M pro previous computational works, wherein Michael acceptors , and ketoamides , were investigated, suggested that the physiological PT reaction from Cys145 to His41 occurs prior to covalent binding of the inhibitor.…”
mentioning
confidence: 99%
“…Some classes of inhibitors of SARS-CoV-2 M pro , such as Michael acceptors and ketoamides, , also require a deprotonated Cys145 to covalently bind the active site. Diverse binding mechanisms between inhibitors and enzymes featuring an active-site cysteine have been reported, either involving a direct PT reaction between the inhibitor and the cysteine or requiring a PT reaction from the cysteine to a protein base prior to the binding reaction . In the case of SARS-CoV-2 M pro previous computational works, wherein Michael acceptors , and ketoamides , were investigated, suggested that the physiological PT reaction from Cys145 to His41 occurs prior to covalent binding of the inhibitor.…”
mentioning
confidence: 99%
“…Given the challenges associated with simultaneous treatment of electronic structure and sampling, multi-scale QM/MM MD is typically employed with both small QM regions (e.g., 30-60 atoms [82][83][84]) and with low-cost, semi-local DFT [85] or semi-empirical QM [86][87][88] (e.g., PM6 or DFTB [89]). To carry out free energy simulations, umbrella sampling has been used by multiple groups [86,87,90] along the methyl transfer coordinate of catechol O-methyltransferase (COMT, Figure 4).…”
Section: Ab Initio and Multi-scale Molecular Dynamicsmentioning
confidence: 99%
“…Over the last decade, BTK inhibitors have demonstrated e cacy and tolerability in the treatment of B cell malignancies (especially in relapsed or refractory cases [5]), including in chronic lymphocytic leukemia [6,7], diffuse large B cell lymphoma [8], mantle cell lymphoma [9], multiple myeloma [10], and follicular lymphoma [11]. Ibrutinib is the rst covalent irreversible inhibitor of BTK to be used in the treatment of Bcell cancers [12], and it showed anticancer activity in relapsed/refractory multiple myeloma patients when combined with car lzomib/dexamethasone [13][14][15][16]. Three additional agents targeting BTK have been developed: zanubrutinib (BGB-3111) [17], acalabrutinib (ACP-196) [18], and tirabrutinib (ONO/GS-4059) [19].…”
Section: Introductionmentioning
confidence: 99%